Simulation based design of optimal phasing plans for an intersection with semi-actuated signals - Maria de Lurdes Simões (2009)
The main problem when using semi-actuated control is the difficulty in selecting the best combination of maximum, minimum and unit extension of green time. In this research a microscopic simulation program has been used for evaluating operating conditions and for estimating vehicular delay at an isolated signalized intersection with semi-actuated control. We analyse the influence of the unit extension and the maximum green time in the total vehicular delay in the intersection and determine the best combination of values for these two parameters. We conclude that, for the intersection under study, the best timing plan includes a unit extension of 4 seconds and the maximum green time must be equal to 40 seconds. (c) Civil-Comp Press, 2009.